Modifications of physical properties in dry Chaco entisols for the recovery of degraded rangelands (Semiárida, 2024)
The objective of the study was to assess the impact of different soil decompaction tools (disc coulter and roller chopping) and manure application on the infiltration and soil compaction (RSP) in Buffel grass (Cenchrus ciliaris) pastures in the Argentine Dry Chaco. The trial was carried out on pastures more than 10 years old, because it was observed that production decreases after this age. Soil sampling was carried out during two consecutive years at the end of the dry season (lower soil moisture). The experimental design had two factors: Tillage (three levels, roller chopping, disc coulter and no tillage) and manure addition (two levels, Yes/No). The hypothesis was that decompaction and manure addition would produce a decrease in compaction and an increase in infiltration returning the grassland to productivity. The results show that the variables analyzed were modified, showing a decrease in RSP with a difference for Tillage (p < 0.0002), ordered as follows with tilling < no tilling, no differences were found for the Manure Addition factor, the trend shows with manure < no manure, for infiltration there is also a correspondence in finding an increase in the treatments with Tilling (p
Keywords: Buffel grass; Compaction; Infiltration